Selective clearance of aberrant tau proteins and rescue of neurotoxicity by transcription factor EB. Issue 9 (28th July 2014) - Polito, Vinicia A; Li, Hongmei; Martini‐Stoica, Heidi; Wang, Baiping; Yang, Li; Xu, Yin; Swartzlander, Daniel B; Palmieri, Michela; di Ronza, Alberto; Lee, Virginia M‐Y; Sardiello, Marco; Ballabio, Andrea; et al.
Abstract Accumulating evidence implicates impairment of the autophagy‐lysosome pathway in Alzheimer's disease (AD). Recently discovered, transcription factor EB (TFEB) is a molecule shown to play central roles in cellular degradative processes. Here we investigate the role of TFEB in AD mouse models. In this study, we demonstrate that TFEB effectively reduces neurofibrillary tangle pathology and rescues behavioral and synaptic deficits and neurodegeneration in the rTg4510 mouse model of tauopathy with no detectable adverse effects when expressed in wild‐type mice. TFEB specifically targets hyperphosphorylated and misfolded Tau species present in both soluble and aggregated fractions while leaving normal Tau intact. We provide in vitro evidence that this effect requires lysosomal activity and we identify phosphatase and tensin homolog (PTEN) as a direct target of TFEB that is required for TFEB‐dependent aberrant Tau clearance. The specificity and efficacy of TFEB in mediating the clearance of toxic Tau species makes it an attractive therapeutic target for treating diseases of tauopathy including AD.